2008
DOI: 10.1111/j.1745-7270.2008.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ecdysis-triggering hormone gene with a binaryUAS/GAL4RNA interference system leads to lethal ecdysis deficiency in silkworm

Abstract: Ecdysis-triggering hormone (ETH) is an integration factor in the ecdysis process of most insects, including Bombyx mori (silkworm). To understand the function of the ETH gene in silkworm, we developed an effective approach to knockdown the expression of ETH in vivo based on RNA interference (RNAi) and a binary UAS/GAL4 expression system that has been successfully used in other insect species. Two kinds of transgenic silkworm were established with this method: the effector strain with the ETH RNAi sequence unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, heat-inducible promoters such as Dmhsp70 have been used to control transcription of dsRNA expression-cassettes in B. mori [47]. Likewise, Gal4-mediated expression of UAS-regulated dsRNA expression-cassettes has been used to efficiently regulate gene expression in specific tissue and temporal patterns [48]. Collectively, these results demonstrate that the transgenic RNAi system can serve as a powerful tool when used alone or jointly with other technologies for gene expression analyses that benefit from the creation of hypomorphic or loss-of-function genotypes and phenotypes.…”
Section: (C) Transgenic Rna Interference-based Gene Silencing Technologymentioning
confidence: 99%
“…For example, heat-inducible promoters such as Dmhsp70 have been used to control transcription of dsRNA expression-cassettes in B. mori [47]. Likewise, Gal4-mediated expression of UAS-regulated dsRNA expression-cassettes has been used to efficiently regulate gene expression in specific tissue and temporal patterns [48]. Collectively, these results demonstrate that the transgenic RNAi system can serve as a powerful tool when used alone or jointly with other technologies for gene expression analyses that benefit from the creation of hypomorphic or loss-of-function genotypes and phenotypes.…”
Section: (C) Transgenic Rna Interference-based Gene Silencing Technologymentioning
confidence: 99%
“…Additional functions of the ETH have recently been uncovered for the regulation of another crucial endocrine factor, juvenile hormone (JH) in Dipteran insects (Areiza et al ., 2014 ; Nouzova et al ., 2018 ) as well as for the control of reproduction (Areiza et al ., 2014 ; Nouzova et al ., 2018 ; Shi et al ., 2019 ). Most of all, disruption of this signaling system has been demonstrated to be lethal to many species of insects (Park et al ., 2002a ; Dai et al ., 2008 ; Lenaerts et al ., 2017 ; Shi et al ., 2017 ; Shen et al ., 2021 ), offering a potential target system for development of an insecticidal strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of the chitin synthase gene by RNAi has been found to disrupt the larval development of Spodoptera exigua (Chen et al 2008). Whereas knockdown of the ecdysis regulatory gene with a binary UAS/GAL4 RNAi system led to lethal ecdysis deficiency in silkworm (Dai et al 2008). Host-delivered hpRNA-mediated resistance to pod borer was few studies reported AChE2 as the primary catalytic enzyme in some other insect species (Kim and Lee 2013).…”
Section: Introductionmentioning
confidence: 99%